The U.S. National Tips From Former Smokers Antismoking Campaign: Promoting Awareness of Smoking-Related Risks, Cessation Resources, and Cessation Behaviors. (August 2015) - Huang, Li-Ling; Thrasher, James F.; Abad, Erika Nayeli; Cummings, K. Michael; Bansal-Travers, Maansi; Brown, Abraham; Nagelhout, Gera E.
Objective . Evaluate the second flight of the U.S. Tips From Former Smokers (Tips) campaign. Method . Data were analyzed from an online consumer panel of U.S. adult smokers before ( n = 1, 404) and after ( n = 1, 401) the 2013 Tips campaign launch. Generalized estimating equation models assessed whether the Tips advertisement recall was associated with knowledge about smoking-related risks in the Tips advertisements, awareness and use of a toll-free quitline and cessation websites, and quit attempts. Results . Seventy-one percent of participants at Wave 2 reported that they recalled seeing at least one Tips advertisement. Smokers who recalled seeing a Tips advertisement were more likely to (a) show increases over baseline in knowledge of health risks such as amputation: 65% versus 34%, p < .001; blindness: 27% versus 12%, p < .001; and (b) to be aware of a quitline (41% vs. 30%, p < .001) and cessation website (28% vs. 20%, p < .001). Recall of Tips advertisements was also associated with greater likelihood of reporting having visited cessation websites (odds ratio [OR] = 1.62, 95% confidence interval [CI] = 1.27-2.06), having called a quitline (OR = 2.28, 95% CI = 1.61-3.24), and having made a quit attempt (OR = 1.18, 95% CI = 1.00-1.39), although these results were only statistically significant in the unadjusted models. Conclusions . The 2013 Tips campaign was successful in increasing knowledge of health risks and awareness of tobacco cessation resources.